КОМПРЕСІЙНА АСФІКСІЯ - Хоботова Наталія Володимирівна; Єхалов Василій Вталійович (International Academy Journal Web of Scholar, 2019)
Compression asphyxia is a type of mechanical asphyxia when breathing stops with external pressure on the body, which leads to the absence of respiratory movements and disrupts venous return from the head. With a strong compression of the chest, a reflex spasm of the glottis occurs, which contributes to an increase in intrathoracic pressure, reverse venous blood flow and an obstruction of venous flow to the heart occur. A sharp increase in intracranial pressure and venous congestive congestion / hemorrhage deepen central respiratory failure. Mild degree: mental agitation; puffy face, slight cyanosis; individual conjunctival petechiae; tachypnea. Medium degree: light or heavy stunning, lost orientation; the face is puffy, cyanotic; swelling of the cervical veins, acrocyanosis; multiple petechiae that spread across the face, neck, conjunctiva of the eyes, inspiratory dyspnea, visual impairment. Severe degree: stupor or coma, sharp cyanosis of the whole body, exophthalmos; swelling of the face, neck and shoulder girdle, arms, multiple petechiae of the face, neck, arms, legs, conjunctiva of the eyes, swelling of the cervical veins, cyanosis and edema of the upper half of the body; superficial breathing, frequent, in the absence of treatment passes to agonal and apnea. Intensive care includes analgesia, oxygenation or mechanical ventilation, anticonvulsant, dehydration and decongestant therapy, prevention of acute kidney damage, DIC, septic complications, and treatment of posthypoxic encephalopathy.